Peningkatan Kemampuan Menghafal Anak Usia Sekolah Dasar melalui Metode Pair Check - Nur Nafisatul Fithriyah; Lailatul Mamluchah (MODELING: Jurnal Program Studi PGMI, 2020)
The purpose of this study is to improve the ability to memorize early childhood through the pair check method in class IV-B even semester 2017-2018 MINU Berbek Surabaya. Pair check method is a method to strengthen memorization by listening to each other in turn. Specifically, the ability to memorize referred to in this study is that children are able to memorize correctly. This research is a classroom action research method that follows the lewin kurt model. This research consists of two cycles. Each cycle includes 4 stages, namely, 1) planning (planning), 2) action (acting), 3) observation (observing), 4) reflection (reflecting). The time of the study is 1 month, from November 2017 with the subject of research in class IV-B, while the data were collected through non-test assessments, observations, interviews, and documentation. The results showed that there was a significant increase in the ability to memorize in fourth grade students. This can be proven by increasing the results of quantitative calculations starting from the average results of the ability to memorize pre-cycle, cycle 1 to cycle 2, namely the results of the average pre-cycle = 71, cycle 1 = 79, cycle 2 = 87 and the interview results concluded that the method pair check can improve the ability to memorize early childhood optimally. This study concludes that the ability to memorize with the pair check method can improve the ability to memorize early childhood.